Reactive Oxygen Species in the Paraventricular Nucleus of the Hypothalamus Alter Sympathetic Activity During Metabolic Syndrome - Cruz, Josiane C.; Flôr, Atalia F. L.; França-Silva, Maria S.; Balarini, Camille M.; Braga, Valdir A. (Frontiers in Physiology, 2015)
The paraventricular nucleus of the hypothalamus (PVN) contains heterogeneous populations of neurons involved in autonomic and neuroendocrine regulation. The PVN plays an important role in the sympathoexcitatory response to increasing circulating levels of angiotensin II (Ang-II), which activates AT1 receptors in the circumventricular organs (OCVs), mainly in the subfornical organ (SFO). Circulating Ang-II induces a de novo synthesis of Ang-II in SFO neurons projecting to pre-autonomic PVN neurons. Activation of AT1 receptors induces intracellular increases in reactive oxygen species (ROS), leading to increases in sympathetic nerve activity (SNA). Chronic sympathetic nerve activation promotes a series of metabolic disorders that characterizes the metabolic syndrome (MetS): dyslipidemia, hyperinsulinemia, glucose intolerance, hyperleptinemia and elevated plasma hormone levels, such as noradrenaline, glucocorticoids, leptin, insulin and Ang-II. This review will discuss the contribution of our laboratory and others regarding the sympathoexcitation caused by peripheral Ang-II-induced reactive oxygen species along the subfornical organ and paraventricular nucleus of the hypothalamus. We hypothesize that this mechanism could be involved in metabolic disorders underlying MetS.